Illuminating the "Brain Rot" in the Logic of Hope as a Transcendental Human Force: A Critical Philosophical Analysis of Cognitive Decline in the Digital Era - Ignasius Ngari; Yohanes Kore; Maximilianus Bos Pegan (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The phenomenon of “brain rot” the decline of intellectual abilities due to excessive consumption of shallow digital content has become a global concern after being named Oxford Dictionary’s Word of the Year 2024. Although digital cognitive decline has been widely documented, its philosophical dimension, particularly the role of hope as a transcendental counter-force, remains underexplored. Objective: This study analyzes brain rot philosophically and proposes recovery strategies through hope as a transcendental human force, using the Pandora’s box metaphor. It argues that hope understood as an active cognitive-affective disposition rather than passive optimism forms the philosophical basis for resisting and recovering from brain rot. Methods: This research employs a qualitative philosophical approach utilizing conceptual analysis, comparative philosophical analysis, and critical hermeneutic analysis. In-depth examination is conducted on the thoughts of philosophers regarding hope (Kant, Kierkegaard, Marcel, Fromm, Bloch, Byung Chul Han) as well as negative conceptions (Spinoza, Schopenhauer, Nietzsche, Camus). Results: Hope is an active mindset that motivates action and enables individuals to mobilize social, cultural, and institutional resources. Strategies to overcome brain rot include improving digital literacy, limiting screen time, balancing digital and non-digital activities, developing diverse interests, strengthening social relationships, and engaging in physical activity. Conclusion: This study proposes hope as a philosophical basis for cognitive recovery in the digital era. Despite cognitive degradation caused by digital culture, hope remains a liberating force that helps individuals overcome despair and restore cognitive agency. Further empirical research is needed to validate these ideas across different cultural contexts.